Dye wastewater treatment driven by cyclically heating/ cooling the poled (K0.5Na0.5)NbO3 pyroelectric crystal catalyst. (10th December 2020) - Ma, Jiangping; Jia, Yanmin; Chen, Lin; Zheng, Yangqiong; Wu, Zheng; Luo, Wenshu; Jiang, Minhong; Cui, Xiangzhi; Li, Yanxi
Abstract: In this work, a novel pyroelectric catalysis technique is developed for decomposition of dye wastewater using the lead-free (K0.5 Na0.5 )NbO3 pyroelectric crystal catalyst under the environmental temperature variation. 91.2% of rhodamine B dye can be decomposed after (K0.5 Na0.5 )NbO3 pyroelectric catalyst undergoing 100 cold-hot 30–60 °C cycles. The catalytic activity can be obviously influenced by the poling electric field of catalyst materials. With the increase of the poling electric field from 0 to 4.5 kV/mm, the dye decomposition ratio correspondingly increases from 3.3% to 91.2%. The poling treatment is helpful to enhance the polarization of the (K0.5 Na0.5 )NbO3 crystal, which can also result in the increase of the pyroelectric coefficient, yielding to the enhancement of pyroelectric catalysis. The scavenger experiments are carried out, in which the main active species in the pyroelectric catalysis are found to be superoxide radicals, hydroxyl radicals and holes. The effects of various factors including dye concentration, catalyst dosage, pH and type of dyes on pyroelectric catalysis performance of (K0.5 Na0.5 )NbO3 are also investigated to obtain the optimum condition. The results of three consecutive recycling-utilization tests indicate that (K0.5 Na0.5 )NbO3 crystal possesses good chemical stability. With these advantages of high dye decomposition ratio and good recycling utilization, (K0.5 Na0.5 )NbO3 crystal is potential in developing the novel pyroelectric catalysis technique for decomposition of dye wastewater through utilizing the thermal energy from the environmental cold-hot temperature variation in future. Graphical abstract: Image 1 Highlights: Temperature variation-induced pyroelectric catalysis is discovered in (K0.5 Na0.5 )NbO3 crystal. The pyroelectric catalysis of (K0.5 Na0.5 )NbO3 can be influenced through electric poling. Electric field poling shows great potential in the preparation of pyroelectric catalysts. It is desirable to realize dye wastewater purification through ultilizing cold-hot alternation.